Field Observations During the Ninth Microwave Water and Energy Balance Experiment (MicroWEX-9): from March 24, 2010 through January 6, 2011 - Tara Bongiovanni; Pang-Wei Liu; Karthik Nagarajan; Robert Terwilleger; Alejandro Monsivais-Huertero; Jasmeet Judge; Juan Fernandez-Diaz; Daniel Preston; Tyler Cheney; Jason Motsinger (EDIS, 2013)
The goal of MicroWEX-9 was to conduct a season-long experiment that incorporated passive microwave observations as well as Light Detection and Ranging (LiDAR) observations for a growing season of elephant grass. The variety of sensors would allow for further understanding of the land-atmosphere interactions during the growing season, and their effect on observed passive microwave signatures at 6.7 GHz and 1.4 GHz, as well as LiDAR scans. This 72-page fact sheet was written by Tara Bongiovanni, Pang-Wei Liu, Karthik Nagarajan, Robert Terwilleger, Alejandro Monsivais-Huertero, Jasmeet Judge, Juan Fernandez-Diaz, Daniel Preston, Tyler Cheney, Jason Motsinger, and published by the UF Department of Agricultural and Biological Engineering, January 2013.